Investigating the effectiveness of liquid rubber as a modifier for asphalt binder. Issue 4 (1st October 2016) - Fini, Elham H.; Hosseinnezhad, Shahrzad; Oldham, Daniel J.; Sharma, Brajendra K.
Abstract : Rubber modification of asphalt is one of the most common asphalt modifications used to improve asphalt rheological properties; in such applications, rubber is mainly introduced to the asphalt matrix as a solid particulate matter and referred to as crumb rubber (CR) via wet or dry processing. However, the application of solid CR particles can cause such challenges as phase separation and segregation within the asphalt matrix. Accordingly, this paper investigates the feasibility of application of liquid rubber (LR) produced through vacuum pyrolysis of scrap tyre as an asphalt modifier. The LR used in this paper is recovered from rubber vacuum pyrolysis after the separation of its light compounds for fuel application. During the pyrolysis process, high chain hydrocarbons of rubber transform into short-chain molecules. Although asphalt modified by LR still benefits from the presence of styrene butadiene rubber components in LR. As such, this paper investigates the physio-chemical properties of LR as well as rheological properties of liquid rubber-modified (LRM) asphalt as affected by the presence of short-chain and low-molecular weight hydrocarbons found in rubber. In addition, Fourier transform infrared spectroscopy analysis was used to track the content of rubber polymer and other hydrocarbons inside LRM asphalt. Thin-layer chromatography with flame ionisation detection was used to determine the saturates, aromatics, resins, and asphaltenes components of LRM. Gel permeation chromatography showed the molecular weight distribution of LR and molecular size distribution of LRM with different percentages of LR. Thermal gravimetric analysis was performed to obtain the thermal decomposition temperatures for both modified and unmodified specimens. Furthermore, rotational viscometer, dynamic shear rheometer, multiple stress-creep recovery, and bending beam rheometer were used to evaluate rheological properties of LRM asphalt. The study results showed that introduction of LR to the asphalt matrix can improve its rheological properties while enhancing its low-temperature characteristics.